Modelling Train Station Choice under Uncertainty for Park and Ride Users - Chen, Chunmei (Curtin University, 2019)
This research develops a novel theoretical framework for modelling train station choice under uncertainty for park and ride users. Three uncertain factors, travel time to station, parking search time and crowding on trains, are modelled to estimate station choice probabilities, the risk attitudes of respondents and the preference heterogeneity of individuals. This study may support planning decisions on the location, price and capacity of P&R facilities, and provide evidence for evaluating P&R investment decisions.